Open Letter to U.S. President Donald J. Trump: Deep-State Devastation of Human and Environmental Health - Herndon, J. Marvin (European Journal of Applied Sciences, 2025)
One of the primary purposes of the U.S. Constitution, as set forth in its Preamble, is to “promote the general welfare.” Yet, for at least two decades, as evidenced in this document and its references, the Deep-State, including components of the U.S. military, NOAA and its predecessors, the CIA, NASA, EPA and other U.S. agencies, together with corresponding foreign entities, have been engaged in a widespread, massive-scale, covert activity poisoning the air we breathe with an extremely toxic substance that has been implicated in numerous very serious human and environmental health problems. Although said extremely toxic substance is a closely guarded secret, by sound scientific methodology, we have discovered the identity of said toxic substance, evidenced as coal fly ash, and its grievous adverse consequences on human and environmental health as reviewed here.